Business process and innovation management: the situation of SMEs in Italy. (2019) - Broccardo, Laura; Culasso, Francesca; Truant, Elisa
Business process management (BPM) is recognised as highly valuable, although not yet widely implemented by companies, with significant differences existing between small and large enterprises. The purpose of this research was to investigate the increasing use of BPM, focusing on innovation in small and medium enterprises (SMEs), an aspect not widely dealt with in the literature. The method used was a survey by questionnaire, conducted on a sample of Italian SMEs. The findings pointed to inadequate use of BPM and scant awareness of potential benefits to be gained from investment in research and development. This study was meant to contribute to the literature on these subjects, which are not particularly structured, and help in bridging the gap with evidence from the local context. Moreover, SME management should be more aware of the importance of process and innovation management in achieving sustainable growth.